Cultivable Anaerobic Microbiota of Infected Root Canals - Takuichi Sato; Keiko Yamaki; Naoko Ishida; Kazuhiro Hashimoto; Yasuhisa Takeuchi; Megumi Shoji; Emika Sato; Junko Matsuyama; Hidetoshi Shimauchi; Nobuhiro Takahashi (Hindawi Limited, 2012)
Objective. Periapical periodontitis is an infectious and inflammatory disease of the periapical tissues caused by oral bacteria invading the root canal. In the present study, profiling of the microbiota in infected root canals was performed using anaerobic culture and molecular biological techniques for bacterial identification. Methods. Informed consent was obtained from all subjects (age ranges, 34-71 years). Nine infected root canals with periapical lesions from 7 subjects were included. Samples from infected root canals were collected, followed by anaerobic culture on CDC blood agar plates. After 7 days, colony forming units (CFU) were counted and isolated bacteria were identified by 16S rRNA gene sequencing. Results. The mean bacterial count (CFU) in root canals was (0.5±1.1)×106 (range 8.0×101-3.1×106), and anaerobic bacteria were predominant (89.8%). The predominant isolates were Olsenella (25.4%), Mogibacterium (17.7%), Pseudoramibacter (17.7%), Propionibacterium (11.9%) and Parvimonas (5.9%). Conclusion. The combination of anaerobic culture and molecular biological techniques makes it possible to analyze rapidly the microbiota in infected root canals. The overwhelming majority of the isolates from infected root canals were found to be anaerobic bacteria, suggesting that the environment in root canals is anaerobic and therefore support the growth of anaerobes.